Mnogo hrupa za nič (1. del): potek in ozadje odkritja "staroslovanskega svetišča" na ptujskem gradu - Janžekovič, Izidor (Zgodovinski časopis, 2017)
A still unresolved heated discussion took place nearly 70 years ago in the second and third issue of the Historic Review. It is one of the most controversial archaeological issues in Slovenia, i.e. the problem of the so-called Slavic sanctuary in Ptuj. Author presents the vibrant background of the discovery in the post-war Yugoslavia during the big archaeological excavations on the western plateau of the Ptuj Castle. Excavations are presented in a bigger context of the post-war (re)building of the state and nation (of Yugoslavs), as archaeologists and historians laid new foundations of new state.
Keywords: 19./20.st.; archaeological excavations; arheološka izkopavanja; arheološke najdbe; gradovi; late antiquity; Medieval tower; Middle ages; post-war period; pozna antika; Ptuj; Ptuj castle; slavic sanctuary; Slavs; slovansko svetišče; srednjeveški stolpi; srednji vek; Yugoslavia